2022
DOI: 10.3233/wor-220112
|View full text |Cite
|
Sign up to set email alerts
|

A study on the changes in life habits, mental health, and sleep quality of college students due to COVID-19

Abstract: BACKGROUND: In early 2020, the coronavirus 2019 (COVID-19) pandemic necessitated changes in social behavior to prevent its spread, including holding online classes, implementing social distancing, and allowing employees to telecommute. However, these changes have had a negative impact on people’s sleep patterns and mental health, particularly for college students. OBJECTIVE: This study investigated the relationship between mental health and sleep quality according to the changes in lifestyle of college student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…These results suggest that students with moderate to severe insomnia are more likely to report high levels of depression. This study thus confirms other studies' findings of a strong correlation between the ISI and depressive symptoms [3,10,11,14,34,39,41,54]. High factor loadings and acceptable AVE and CR values also verified the convergent validity of the ISI.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These results suggest that students with moderate to severe insomnia are more likely to report high levels of depression. This study thus confirms other studies' findings of a strong correlation between the ISI and depressive symptoms [3,10,11,14,34,39,41,54]. High factor loadings and acceptable AVE and CR values also verified the convergent validity of the ISI.…”
Section: Discussionsupporting
confidence: 90%
“…Compared with the overall population, university students have perhaps been significantly burdened by COVID-19 regarding their sleep quality and mental health as they have engaged in the most significant variation of activities before and after the pandemic [12,14,15]. A recent study in Korea revealed that sleep quality among university students has severely deteriorated since the start of the COVID-19 pandemic [14]. Generally, the transition from high school to college is a critical risk period commonly associated with the initiation and escalation of substance use [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Petrie et al (2023) showed that patients with sleep problems have a state of daily anxiety and depression, which can lead to prolonged sleep onset, reduced sleep duration and reduced sleep efficiency (McLeish et al, 2023). In turn sleep deprivation can cause physical and mental anxiety arousal to intensify the situation (Lee et al, 2022), and the vicious cycle repeats itself week after week, which is consistent with our finding that anxiety and depression can predict sleep quality. Therefore, schools can reduce the degree of anxiety and depression through psychological counselling for college students, thus improving sleep quality.…”
Section: Discussionsupporting
confidence: 82%
“…More studies saw decreased use of meal delivery apps 34,38,46,48,57 compared to an increase in use 38,49,55 . From the second half of 2021 to the last quarter of 2022, all study outcomes showed an increase in use of online groceries and meal delivery apps 41,60,72,76,79,82,83 …”
Section: Resultsmentioning
confidence: 99%